A Scoping Review of Self-Awareness Instruments for Acquired Brain Injury - Danielle Mahoney; Sharon A. Gutman; Glen Gillen (Scholarworks @ WMU, 2019)
Background: Self-awareness and insight are critical functions required to maintain safe and optimal participation in all daily life activities in a variety of environmental contexts. In the past two decades, occupational therapists have developed several psychometrically sound assessments designed to identify self awareness and insight deficits in patients with neurological disorders. This scoping review identifies and evaluates key properties of such assessments to inform clinical practice. Method: Multiple electronic databases were searched using the key search terms of "self-awareness" and "selfawareness assessment," and "insight" and "insight assessment." Included studies were original primary sources from the peer-reviewed journals. Results: Nine assessments met the inclusion criteria: Assessment of Awareness of Disability, Awareness Interview, Awareness Questionnaire, Insight Interview, Patient Competency Rating Scale, Patient Competency Rating Scale for Neuro-Rehabilitation, Patient Distress Scale, Self-Awareness of Deficits Interview, and Self-Regulation Skills Interview. Each assessment is reviewed in detail regarding its purpose, administration time, format, type of awareness assessed, psychometric properties, and advantages and disadvantages. Conclusions: Although all nine assessments are psychometrically sound, some may hold more usefulness for occupational therapists depending on a variety of factors, including patient cognitive level and activity tolerance and clinical setting and time constraints.